Music’s Vibratory Enchantments and Epistemic Injustices. Reflecting on Thirty Years of Feminist Thought in Music Theory - Judy Lochhead (Zeitschrift der Gesellschaft für Musiktheorie)
Music is often described as having magical powers to enchant listeners, but it has an equally and often unremarked magical effect on performers and scholars contemplating music. North American music theory has done little to address music’s enchantments, preferring to frame its discourse around empiricism and objectivity. Since the 1990s various postmodern and post-structuralist perspectives have brought about changes of content – what music is considered – and methodology, including a consideration of music’s “magical” powers. These new perspectives have, in part, resulted in an increased diversity in the demographics of musicology, but there have not been changes of sufficient significance in either content or methodology in North American music theory and the demographics of music theory remain dominated by white, male practitioners. In this short essay, I propose two ways that music-theoretical practice can be transformed in order to overcome the “epistemic injustices” of past work in music theory. First, music-theoretical work should address the complicity of the scholar’s perspective, and second, it should recognize the authorial work of diverse creators. To exemplify the latter, I offer a short analysis of Eliza Brown’s The Body of the State (2017).